2008
DOI: 10.1002/lt.21437
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of a heparin-like effect shown on the thromboelastograph in patients undergoing liver transplantation

Abstract: It has been known for several decades that thromboelastographic analysis of the blood of patients undergoing liver transplantation may show a heparin-like effect (HLE) at the time of reperfusion. However, the prevalence of HLE and the origin of these heparin-like substances remain largely unstudied. The primary aim of this retrospective observational analysis was to determine the prevalence of the HLE in 211 consecutive patients having liver transplantation in our institution at various stages throughout the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…In this study, CT enlargement in the INTEM after reperfusion was represented in more than 53% of the patients due to the effect of heparin, in agreement with the study of Agarwal et al [35] where they demonstrated in a retrospective and observational study of 211 patients undergoing liver transplantation that the prevalence of heparin was demonstrated in more than 80% of cases after reperfusion of the graft.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, CT enlargement in the INTEM after reperfusion was represented in more than 53% of the patients due to the effect of heparin, in agreement with the study of Agarwal et al [35] where they demonstrated in a retrospective and observational study of 211 patients undergoing liver transplantation that the prevalence of heparin was demonstrated in more than 80% of cases after reperfusion of the graft.…”
Section: Discussionsupporting
confidence: 92%
“…This may be more pronounced with marginal grafts from DCD donors and with significant hepatic-ischaemic-reperfusion insult [46] . The clinical significance of the HLE is not fully understood but it usually resolves spontaneously by the end of the case in the context of a good functioning graft [47] . Hyperfibrinolysis is common due to an increase in tPA from the new liver and decreased production of antifibrinolytic factors and may be associated with increased bleeding [48] .…”
Section: Donohue CI Et Al Reducing Transfusion Requirements In Livementioning
confidence: 99%
“…Coagulation abnormalities during orthotopic liver transplanation are characterised by decreased coagulation factors, antifibrinolytic factors and endogeneous anticoagulant factors [1], all of which represent a major perioperative challenge as both bleeding episodes and thrombotic events can be precipitated [2,3]. Accordingly, monitoring of the coagulation system during liver transplantation is important.Besides standard laboratory methods, point of care assays are gaining increasing acceptance since their results are rapidly available [4][5][6][7][8]. However, only sparse information is available on the comparability of point of care coagulation assays with laboratory coagulation assays in this special setting.…”
mentioning
confidence: 99%
“…Besides standard laboratory methods, point of care assays are gaining increasing acceptance since their results are rapidly available [4][5][6][7][8]. However, only sparse information is available on the comparability of point of care coagulation assays with laboratory coagulation assays in this special setting.…”
mentioning
confidence: 99%